Exhibition of Japanese Artists abroad Europe and America. (Tokyo : The National Museum of Modern Art, 1965)
Abe, Nobuya ; Chiba, Sho ; Azuma, Kenjiro ; Toyofuku, Tomonori ; Yasuda, Haruhiko ; Fujita, Yoshiba ; Sasaki, Shiro ; Iida, Yoshikuni ; Izumi, Shigeru ; Imai, Toshimitsu ; Kito, Akira ; Kimura, Chuta ; Sato, Kei ; etc.
Exhibition of Japanese artists abroad, Europe and America, October 15-November 28, 1965, the National Museum of Modern Art, Tokyo.
English-Japanese
kunstcatalogus
Keywords: Japan